DESIGN OF PROTOTYPE ELECTRICAL FIRING DEVICE SMOKE POWDER BOMB INTEGRATED IN ANDROID - Endin Tri Hartanto; Bagus Irawan; Sunarta Sunarta; Atet Saputra (JOURNAL ASRO, 2020)
Threats are any businesses and activities, both from domestic and foreign countries which are consideredendangering the Indonesian sovereignty, the territorial integrity of the country, and the safety of the wholenation. Military threats are threats that use organized armed forces that are judged to have abilities thatjeopardize the country's sovereignty, the territorial integrity of the country, and the safety of the whole nation.This smoke powder firing system is to utilize the internet network so that to trigger the smoke powder bomb canbe carried out from various places and anywhere the smoke powder weapons ignition can be carried out.Design and Composite Smoke Powder as a Marine, Air and Ground Defense Sabotage Weapon. This researchis expected to be able to contribute to sabotage cysts and deception of opponents. The main objective in thedesign of the building of Smoke Powder as a means of supporting smoke bomb training in a pattern to trick theenemy. In planning the bomb lighter system uses an electric lighter which is controlled remotely via an Androidphone call. The lighters used are gas stove lighters with 3 Volt dc battery voltage source. So that themicrocontroller device can regulate the flow of current to the lighter, the author uses a transistor that functionsas switching power sources to the lighter. The command for switching resources to a lighter is obtained from thecommand of an Android device. The test results show the system can work well, even though the constraintsoccur in the system, namely the GSM network which often interrupt.Keywords : Smoke powder, switching, Android, GSM.